Patterns and drivers of the belowground bud bank in alpine grasslands on the Qinghai-Tibet Plateau - Li, Wencheng; Huang, Aiping; Zhou, Tiancai; Liu, Miao; Ma, Sujie; Zhao, Ningning; Wang, Xiangtao; Sun, Jian (Frontiers in Plant Science, 2023)
In grassland ecosystems dominated by asexual plants, the maintenance, renewal, and resistance of plant populations to disturbance are more dependent on the belowground bud bank (BBB). However, the response of the BBB to environmental factors in the alpine grassland of the Qinghai-Tibet Plateau (QTP) is still unknown. Therefore, a transect survey was conducted to measure the size and scale of BBB and 21 factors in the alpine grassland of the QTP. In addition, the critical driving factors of BBB were screened by boost regression tree analysis, and a structural equation model (SEM) was employed to express the path coefficients of the key factors on the BBB size. The results showed that BBB size had no significant geographical pattern in the QTP, and the BBB size was mainly accounted for by soil leucine aminopeptidase (LAP, 17.32%), followed by Margalef and Shannon-Wiener indices of plants (12.63% and 9.24%, respectively), and precipitation (9.23%). SEM further indicated significant positive effects of plant diversity (scored at 0.296) and precipitation (scored at 0.180) on BBB size, and a significant negative effect of LAP (scored at 0.280) on BBB size. Generally, the findings allow for better understanding of the regulated mechanisms of BBB size and the importance of the role of bud bank in the restoration of the grassland ecosystem.